Data from: Retrospective study using magnetic resonance imaging (MRI) to measure depths of acupuncture points in neck and shoulder region - Chou, Pei-Chi; Huang, Yu-Chuen; Hsueh, Chun-Jen; Lin, Jaung-Geng; Chu, Heng-Yi (Dryad, 2015)
Objectives: There are safety issues associated with acupuncture treatment.
Previous studies regarding needling depth of acupuncture points revealed
inconsistent results due to vague depth definition, acupuncture point
localisation and measuring tools. The objective of this study is to find
and compare the differences of the mean depths of 11 acupuncture points in
the neck and shoulder region between subjects, with variables including
gender and body mass index (BMI). Setting: This study was conducted at a
single medical center in Taiwan. Participants: Three hundred and
ninety-four participants were included in this study. Participants were
grouped according to gender and BMI. Acupuncture points were localised by
WHO standard and measured by MRI. Outcome measures: The distance from the
needle insertion point (surface of the skin) to any tissues that would
cause possible/severe complications. Results: Mean depths of 11 points
were obtained in groups of different BMI and gender. Mean depths of all
participants regardless of BMI and gender are as follows, in centimetres:
GB21=5.6, SI14=5.2, SI15=8.8, GV15=4.9, GV16=4.6, GB20=5.0, ST9=1.6,
SI16=1.8, SI17=2.4, TE16=3.1, LI18=1.3. Participants with higher BMI had
greater measured depths in both gender groups. Male participants had
larger mean depths than female participants regardless of BMI except in
SI17 and LI18. When taking BMI into consideration, depths in male
participants are greater than in female participants in most of the points
except the following: GB21, TE16 in obesity group; ST9 in underweight and
obesity group; SI16 in ideal body weight, overweight and obesity group;
SI17, LI18 in each group. Conclusions: Participants with higher BMI had
greater measured depths and males tended to have greater depths in most of
the points. Clinical practitioners are recommended to consider this
information to prevent complications when applying acupuncture treatment
to their patients.
raw data of the study-Retrospective Study using Magnetic Resonance Imaging
(MRI) to Measure Depths of Acupuncture Points in Neck and Shoulder
RegionThis document contains the raw data of 394 subjects including
sex,BMI and measured depth of each point in the study: Retrospective Study
using Magnetic Resonance Imaging (MRI) to Measure Depths of Acupuncture
Points in Neck and Shoulder Region.
Keywords: Magnetic resonance imaging; complementary medicine